Proses Penyelesaian Sengketa Wanprestasi Jual BeliTanah Atas Harta Bersama Yang Belum DibagiSetelah Bercerai (Studi Kasus Pengadilan Negeri Surakarta) - Darmadi, Sigit, Nuswardhani, S.H.,S.U, Septarina Budiwati, S.H.,M.H (2016)
The purpose of this study is to determine how to process a purchase agreement of land if the land is sold it was not land owned by the seller himself, so the seller is declared in default, to know how the judge in determining the evidence associated with defaults sale and purchase of land on property that has not been shared after the divorce, to determine the consideration of Judges in decisions on land purchase in default on property that has not been divided after divorce this study uses normative approach and using a qualitative approach. Descriptive study. Data analysis methods used by the author is a qualitative approach. In the process of making a land purchase agreement there are several steps that must be done, namely First, the preparation phase before the land purchase agreement. Prospective buyers expressed interest in buying the land, then do research on the letters pertaining to land as the object of buying and selling, Second, land transactions can occur due to an agreement or consensus between the seller and the prospective buyer. Third, Stage alienation .. Based on the examination of this trial can be concluded about the results of proof and has obtained the legal facts as follows: proven default event has occurred against the sale and purchase agreement of land disputed is that the Defendant I and Defendant II refused to submit a certificate on the disputed land, whereas the applicant party is already giving money payment for land purchase object of the dispute.